THE EFFECT OF MICORIZA ORGANIC FERTILIZER AND SOLID WASTE (SLUDGE) ON THE GROWTH AND PRODUCTION OF PEANUT (Arachis hypogeaeL.) - Irna Syofia; Fredy Anggara Daulay (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This study aimed to evaluate the response of the growth and production of groundnut (Arachis hypogeae L.) to fertilizer application and mycorrhizal biological solid waste (sludge), field trials conducted at the Faculty of Agriculture, University of North Sumatra Muhammadiyah, sub Sei blue-blue, Deli Serdang regency Province North Sumatra with altitude ± 150 m above sea level, in May and ending in August 2014. This study used a randomized block design (RBD) factorial with two factors: Biological Fertilizer Mycorrhizae (M) with 4 levels, namely: control = M0, M1 = 3 g / plant M2 = 6 g / plant M3 = 9 g / plant and factors giving Solid Waste (Sludge) with 3 levels, namely: S1 = 13ton = 2 kg / plot, S2 = 26 tons / ha = 4 kg / plot, S3 = 39 tons / ha = 6 kg / plot. observation parameters namely: plant height, number of branches, days to flowering, number ginopora, number of pods / plant, number of empty pods / plant, number of pods / plot, weight of pods / plant, weight of pods / plot, and the weight of 100 seeds. The survey results revealed that significantly different biological fertilizer Mycorrhiza on the parameters of plant height, number of branches, days to flowering, number of pods / plant, number of pods / plot, weight of pods / plant, pod weight / dose plots mycorrhizal biofertilizer best of 4 levels of treatment ie the dose 9 g / plant .and solid waste (sludge) was significantly different in the 2 MST parameters seedling height and weight of 100 seeds / plot.